Factors Affecting the Incidence of Scabies in Darul Abror Modern Islamic Boarding School, Kace Village - Hasan, Abdul Kadir; Kartika, Kartika; Djuria, Syafrina Arbaani (PT FORMOSA CENDEKIA GLOBAL, 2023)
World Health Organization (WHO) data shows that the prevalence of scabies in 2014 was 130 million people in the world. Scabies or scabies is a skin disease caused by infestation and sensitization. Scabiei hominis variety. The method used is analytical observational with a case control design. The research was conducted on students at the Al Abror Islamic Boarding School, Kace Village, Bangka Regency.The results of the research showed that the highest age of students was 13 years old, 31 people (51%), the highest education was junior high school, 58 people (96.7%), the length of stay at the boarding school for > 1 year was 59 people (98.3%). Respondents who had good knowledge were 55 people (91.7%), 27 people had an agreeable attitude (45%), 51 people had good personal hygiene behavior (85%), 43 people had good sanitation observations (71.7%). Conclusion: researchers, knowledge, attitudes, personal hygiene behavior and environmental sanitation conditions in Islamic boarding schools both have a big influence on the spread of scabies. Students' knowledge about scabies greatly influences the incidence of scabies because knowledge is a very important source that influences students' thinking patterns and decision-making processes, students' lack of knowledge has a big influence on the spread of scabies skin disease.